New Lights on Prophecy-Pretending and Mimetic Religions in Medieval Islamic North Africa - Mabrouk Chibani Mansouri (Al-Jami'ah: Journal of Islamic Studies, 2025)
This paper addresses the proliferation of prophetic movements and mimetic religions in medieval Islamic North Africa, focusing on the Barghwāṭa and Ghumāra tribes. It critiques medieval Arabic and Orientalist terminologies used to explain this complex issue, arguing that they fail to capture the dynamics of these movements. The paper introduces the concept of mimetic religion to interpret localized prophetic movements that emerged on the periphery of the established religion, namely Islam, retaining its structure while presenting parallel, rather than counteractive, religio-cultural projects. Drawing on primary sources, it highlights how misrule and exploitative practices by early conquerors fueled North African resistance, leading to revolutionary and prophetic movements. It challenges both medieval historiographical reductions of these movements to sectarianism and modern interpretations shaped by French colonial Orientalism, which often reduced them to ethnic or religious conflicts between Arab-Muslim conquerors and indigenous North Africans. By analyzing primary sources and questioning Orientalist biases, the paper emphasizes the interplay of political, economic, social, and cultural factors in shaping North African religious settings. Ultimately, it defines new boundaries for re-contextualizing and re-interpreting mimetic religion as expressive of a complex texture framing religious, cultural, and social nomenclature rooted in local North African indigenous heritage. [Makalah ini membahas proliferasi gerakan-gerakan kenabian dan agama-agama mimetik di wilayah Afrika Utara abad pertengahan, dengan fokus pada suku Barghwāṭa dan Ghumāra. Studi ini mengkritisi terminologi Arab klasik dan orientalis terkait persoalan yang kompleks ini, dengan kesimpulan bahwa terminologi tersebut gagal menangkap dinamika gerakan yang terjadi. Konsep agama mimetik diperkenalkan untuk memahami gerakan-gerakan kenabian lokal yang berkembang di samping agama yang mapan, yaitu Islam, dengan mempertahankan struktur dasar, namun membawa konsep religio-kultural yang sejajar tanpa mengambil posisi kontradiktif. Berdasarkan sumber-sumber primer, tulisan ini menunjukkan bahwa ketidakadilan pemerintahan dan praktik eksploitasi oleh para penakluk awal turut memicu perlawanan di Afrika Utara yang kemudian melahirkan gerakan-gerakan revolusioner dan kenabian. Penulis menolak reduksi historiografi abad pertengahan yang memandang gerakan-gerakan tersebutsebagai bentuk sektarianisme semata, sekaligus menolak interpretasi modern a la orientalisme kolonial Prancis, yang menyederhanakan gerakan-gerakan tersebut menjadi konflik etnis atau agama antara penakluk Arab-Muslim dan masyarakat pribumi Afrika Utara. Tulisan ini menekankan pentingnya interaksi antara faktor politik, ekonomi, sosial, dan budaya dalam membentuk lanskap keagamaan di Afrika Utara. Agama mimetik adalah ekspresi dari tekstur kompleks yang membingkai nomenklatur religius, kultural, dan sosial yang berakar pada warisan budaya lokal masyarakat pribumi Afrika Utara.]